Determining Good Environmental Status under the Marine Strategy Framework Directive: Case study for descriptor 8 (chemical contaminants). (March 2017) - Lyons, B.P.; Bignell, J.P.; Stentiford, G.D.; Bolam, T.P.C.; Rumney, H.S.; Bersuder, P.; Barber, J.L.; Askem, C.E.; Nicolaus, M.E.E.; Maes, T.
Abstract: The European Union Marine Strategy Framework Directive (MSFD) requires individual member states to develop a robust set of tools for defining eleven qualitative descriptors of Good Environmental Status (GES), such as demonstrating that "Concentrations of contaminants are at levels not giving rise to pollution effects" (GES descriptor 8). Adopting the recommendations of the ICES/OSPAR Study Group for the Integrated Monitoring of Contaminants and Biological Effects (SGIMC), we present a case study demonstrating how the proposed approach, using chemical contaminant (metals and polycyclic aromatic hydrocarbons and polychlorinated biphenyls) and biological effects (EROD, bile metabolites and pathology) data in different matrices (sediment and biota), could be used to contribute to the determination of GES in a region of the North Sea region off the east coast of the UK. Highlights: Integrated chemical and biological effects assessment undertaken of a region of the North Sea. Sediment and biota chemistry and contaminant related biological effects followed ICES guidelines. Study demonstrated the potential for the approach to be used to determine Good Environmental Status (GES).